2012
DOI: 10.1371/journal.pone.0028694
|View full text |Cite
|
Sign up to set email alerts
|

Multi-Parametric Analysis and Modeling of Relationships between Mitochondrial Morphology and Apoptosis

Abstract: Mitochondria exist as a network of interconnected organelles undergoing constant fission and fusion. Current approaches to study mitochondrial morphology are limited by low data sampling coupled with manual identification and classification of complex morphological phenotypes. Here we propose an integrated mechanistic and data-driven modeling approach to analyze heterogeneous, quantified datasets and infer relations between mitochondrial morphology and apoptotic events. We initially performed high-content, mul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
33
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(36 citation statements)
references
References 70 publications
3
33
0
Order By: Relevance
“…Although the role of mitochondrial morphology in cellular physiology has become clearer in recent years, the exact morphological behavior of cardiac mitochondria under normal and pathological settings have not been comprehensively studied and are For mainly confined to IMF and SSM mitochondria 13,2023 . Furthermore, the morphological status of mitochondria within cells are directly linked with their function 24,25 instance, H2O2 insult of neonatal rat ventricular myocytes induces a dysregulation of Ca 2+ handling and dissipation of mitochondrial membrane potential which in turn increases the measure of mitochondrial roundness 26 . Similarly, IRI simulation in H9C2 cells has been shown to induce the formation of circular donut shaped mitochondria which possess lower membrane potential and altered K + cannel activity in comparison to their elongated counterparts which further supports the link between the morphology of mitochondria and their function 27 .…”
Section: Resultsmentioning
confidence: 99%
“…Although the role of mitochondrial morphology in cellular physiology has become clearer in recent years, the exact morphological behavior of cardiac mitochondria under normal and pathological settings have not been comprehensively studied and are For mainly confined to IMF and SSM mitochondria 13,2023 . Furthermore, the morphological status of mitochondria within cells are directly linked with their function 24,25 instance, H2O2 insult of neonatal rat ventricular myocytes induces a dysregulation of Ca 2+ handling and dissipation of mitochondrial membrane potential which in turn increases the measure of mitochondrial roundness 26 . Similarly, IRI simulation in H9C2 cells has been shown to induce the formation of circular donut shaped mitochondria which possess lower membrane potential and altered K + cannel activity in comparison to their elongated counterparts which further supports the link between the morphology of mitochondria and their function 27 .…”
Section: Resultsmentioning
confidence: 99%
“…Computerized methods have been developed to rapidly assess mitochondrial dynamics in mammalian cell culture models (Chevrollier et al, 2012; Koopman et al, 2006; Leonard et al, 2015; Lihavainen et al, 2012; Peng et al, 2011; Reis et al, 2012). These methods have clear advantages, including automated fluorescence microscopy followed by high throughput computational binning of mitochondria into distinct morphological subclasses.…”
Section: Introductionmentioning
confidence: 99%
“…Many parametric analytic methods have been used to address this issue, including speckle fluctuation in time-lapse images [2527]. It was confirmed that back-scattering signals are lower in apoptotic cells [28], which is most likely due to the perturbation of mitochondrial morphology during apoptosis [29]. Nuclear disintegration after chromatin condensation provides high-signal-intensity peaks that facilitate the identification of apoptotic cells.…”
Section: Introductionmentioning
confidence: 99%